Rethinking and re-evaluating the purpose of the business school - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2017)
Without doubt, business schools have been one of the success stories of higher education over the past 50 years. Even so, over the past decade management education has come under attack over both its legitimacy as a serious academic discipline, and its failure to professionalise management. Perhaps now is an opportune time, therefore, for management educators to reflect on the value and purpose of business education and address the real issue of how to innovate to improve student learning about both the theory and practice of management.